Analysis of genetic variation in human papillomavirus type 16 E1 and E2 in women with cervical infection in Xinjiang, China - Luyue Wang; Fang Wang; Shaowei Fu; Chunhe Zhang; Xiangyi Zhe; Hongtao Li; Dongmei Li; Renfu Shao; Zemin Pan (BMC, 2021)
Abstract Background Xinjiang is one of the regions with a high incidence of cervical cancer, and the genetic variation of human papillomavirus may increase its ability to infect the human body and enhance virus-mediated immune escape ability. Methods Sanger sequencing of the HPV16 genome from 165 samples positive for HPV16 infection and phylogenetic analysis of the E1 and E2 genes revealed the gene polymorphism of HPV16 in Xinjiang. Results The results showed that there were 109 samples with variations in HPV16 E1, 48 sites with nucleotide variations (19 missense variations and 29 synonymous variations), and 91 samples with variations in HPV16 E2, 25 sites with nucleotide variations (20 missense variations and five synonymous variations). Conclusions From the phylogenetic tree results, 149 samples were of the European variant and 16 samples were of the Asian variant. No African or North American/Asian variant types were found.